Activin Receptor-Like Kinase 7 Suppresses Lipolysis to Accumulate Fat in Obesity Through Downregulation of Peroxisome Proliferator–Activated Receptor γ and C/EBPα - Yogosawa, Satomi (American Diabetes Association, 2013)
We previously identified a quantitative trait locus for adiposity, non-insulin-dependent diabetes 5 (Nidd5), on mouse chromosome 2. In the current study, we identified the actual genetic alteration at Nidd5 as a nonsense mutation of the Acvr1c gene encoding activin receptor-like kinase 7 (ALK7), one of the type I transforming growth factor-β receptors, which results in a COOH-terminal deletion of the kinase domain. We further showed that the ALK7 dysfunction causes increased lipolysis in adipocytes and leads to decreased fat accumulation. Conversely, ALK7 activation inhibits lipolysis by suppressing the expression of adipose lipases. ALK7 and activated Smads repress those lipases by downregulating peroxisome proliferator–activated receptor γ (PPARγ) and CCAAT/enhancer binding protein (C/EBP) α. Although PPARγ and C/EBPα act as adipogenic transcription factors during adipocyte differentiation, they are lipolytic in sum in differentiated adipocytes and are downregulated by ALK7 in obesity to accumulate fat. Under the obese state, ALK7 deficiency improves glucose tolerance and insulin sensitivity by preferentially increasing fat combustion in mice. These findings have uncovered a net lipolytic function of PPARγ and C/EBPα in differentiated adipocytes and point to the ALK7-signaling pathway that is activated in obesity as a potential target of medical intervention.